2016
DOI: 10.1007/s00421-016-3473-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of force depression caused by different types of physical exercise studied by direct electrical stimulation of human quadriceps muscle

Abstract: PurposeForce production frequently remains depressed for several hours or even days after various types of strenuous physical exercise. We hypothesized that the pattern of force changes during the first hour after exercise can be used to reveal muscular mechanisms likely to underlie the decline in muscle performance during exercise as well as factors involved in the triggering the prolonged force depression after exercise.MethodsNine groups of recreationally active male volunteers performed one of the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 47 publications
3
72
0
Order By: Relevance
“…; Skurvydas et al . ). High‐intensity exercise‐induced ROS production has been implicated in the development of PLFFD (Bruton et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Skurvydas et al . ). High‐intensity exercise‐induced ROS production has been implicated in the development of PLFFD (Bruton et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Skurvydas et al . ; Watanabe & Wada, ). Studies in intact single fibres of rodent and amphibian skeletal muscle have revealed the underlying cellular mechanisms of fatigue to be (i) a reduced maximal myofibrillar force‐producing capacity, (ii) an impaired sarcoplasmic reticulum (SR) Ca 2+ release, and (iii) a reduced myofibrillar Ca 2+ sensitivity (Allen et al .…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, peripheral fatigue, i.e., decreases in electrically induced force, also depends on two processes: interactions of muscle potentiation, and fatigue [4,29]. Previous studies have shown that the performance of 100 repetitive maximal voluntary quadriceps muscle contractions leads to assertion of post-tetanic potentiation, low-frequency fatigue, and post-contractile depression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Increased muscle temperature evokes a decrease in involuntary muscle force [27]. In addition, during the time of recovery, an increase in the P20/P100 factor was observed in both groups, indicating a muscle potentiation mechanism before evidential fatigue [4]. This muscle potentiation mechanism may conceal an increase in fatigue-based muscle force sensation, i.e., a higher potentiation leads to a lower force sensation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle that has been subjected to eccentric exercise shows a disproportionate loss of force when electrically stimulated at low, compared to higher, frequencies (Davies & White, 1981;Kamandulis et al, 2017;Newham, Jones, & Clarkson, 1987;Skurvydas et al, 2016). This feature is relatively slow to recover and is often described as long lasting or low frequency fatigue (LFF) and may be a consequence of reduced calcium release in response to individual action potentials (Balnave & Allen, 1995;Edwards, Hill, Jones, & Merton, 1977) indicating some deficit in the mechanism of excitationcontraction (EC) coupling.…”
Section: Introductionmentioning
confidence: 99%